Identitas Alun-Alun Merdeka Sebagai Ruang Publik di Kota Malang - Mutiah Abdat; jenny ernawati (Jurnal Mahasiswa Jurusan Arsitektur, 2018)
Central Bureau of Statistics (BPS) Malang City 2017 mentions that there are 856,410 inhabitants of the city of Malang, within an area of ​​110.06 km2. In addition, there are 100 units of lodging such as hotels and guest houses, 141 units of factories, and 706 units of restaurants and cafes. For a balance development, the city government of Malang began to revitalize urban parks and urban forests into open green public space. This is one of the government's efforts in providing decent public space for the community, mainly supporting the city of Malang as the City of Children's Worth. For example, the Merdeka Square itself has been revitalized in 2015, with considerable physical changes. From its establishment in 1882, the Merdeka Square experienced many physical changes and functions that repeatedly changed its identity. Now with its image as a modern city park, researcher want to know how the identity of the Town Square after the revitalization as a public space according to the user. The method used is mixed method, i.e. observation, place-centered mapping, questionnaire, and cognitive maps. The results shown the identity of Merdeka Square is amphitheater, Jami 'Mosque, and signage "Alun-Alun Malang", circulation paths (Northern path, Western path, and Southern path), and also crowded activities in the amphitheater and playground area. Keywords: public space, place identity, cognitive maps